A Review on Waste Management in Green Computing - Bichaiah, Sindhu (Recent Research Reviews Journal, 2022)
Green Computing, a recent trend and developing industry, is working to create a more sustainable future. Reusable resources are provided through green computing, which is now employed by many different technologies. Green technology is sustainable and eco-friendly. Computer use is growing quickly, which means that computers are using more energy. As a result of higher energy consumption, more eco-harmful carbon footprints are being released into the environment. Due to this issue, many companies having proper way of waste management has started to implement the green computing technologies. This study reviews the different approaches of green computing like energy minimization, virtualization, reduction in use of hazardous substances, and cloud computing. This paper also explains the green computing and its needs. The concern of waste management, which is an approach of green computing can be achieved this way.
Keywords: Green Computing; Waste Management; Environmental hazards; Sustainability